#TITLE_ALTERNATIVE# - 95004029, Meizar NIM.
Abstract : This thesis presents an analysis of water availability in relation with decreasing the cropping intensity of irrigation area. Cirasea irrigation area having a potential area of 2607 acre locates in Ciparay and Bale Endah Sub District, Bandung District West Java Province. Distribution of irrigation water is carried out by applying groups system. The cropping intensity in this irrigation area is still low due to the insufficient of water availability in the main system. Water availability in the main system can not be guarantee to full fill irrigation water requirement for existing total area during all season of cropping mainly in the 2nd cropping season. Water availability is determined base on 20 years water level recording data of Cirasea River, while the irrigation water requirement in calculated by applying water balance method which depend on the several factors, namely; land preparation time, cropping pattern, cropping schedule and the application of groups system. To examine the minimum of difference among water availability and irrigation water requirement, there are 8 alternatives scenario which depend on the cropping pattern, land preparation time and cropping schedule. From the analysis show that the 3rd alternative with cropping pattern Paddy-Paddy-Patawija, land preparation time of 45 days and cropping schedule carried out in the initial month of November are determinate as the most feasible selection, having the minimum water shortage about 404 Us. occurring at the last 2nd cropping season. Net field requirement for lst, 2nd and 3rd cropping season are 0.85 l/s/acre, 0.78 l/s/acre and 0.36 l/s/acre respectively.